Crystallographically Oriented Hybrid Perovskites via Thermal Vacuum Codeposition. Issue 8 (26th June 2021) - Klipfel, Nadja; Momblona, Cristina; Kanda, Hiroyuki; Shibayama, Naoyuki; Nakamura, Yuiga; Mensi, Mounir Driss; Liu, Cheng; Roldán-Carmona, Cristina; Nazeeruddin, Mohammad Khaja
Abstract : Hybrid lead halide perovskites typically form polycrystalline films that have multiple grain sizes and surface defects. A key engineering challenge toward commercialization is therefore the production of homogeneous, defect‐free large‐area devices achieving high efficiency. New market opportunities may arise from vacuum‐deposited perovskites if detailed understanding and control of crystal formation are available. Of the many factors that make reproducibility of device performance difficult, two variables are identified that have not yet been considered in detail: deposition speed and underlayer material selection. Herein, it is demonstrated that small changes in the perovskite growth rate (0.18–0.72 Å·s −1 ) substantially affect the preferred crystal orientation. Further, varying underlayer interfaces greatly influence the composition of the final perovskite and thus its energetic profile. The research aids control in fine‐tuning the perovskite film at the nanometer scale, which enables the reproducible fabrication of vertically aligned and micrometer‐sized grain features, highly demanded for in high‐quality semiconductors. Abstract : The effect of varying underlayer interfaces greatly influences the composition of the methyl ammonium lead iodide (MAPbI3 ) perovskite and thus its energetic profile. Surface chemistry in combination with sublimation speed in vacuum‐deposited MAPbI3 perovskites is evaluated. It is shown that the proper combination of these two variables leads to complete control of the morphology, chemical composition, and crystal alignment.